A Rare Case of Congenital Heart Disease with Bifid Car- diac Apex: A Unique Finding in Left Ventricle - Majid Maleki; Maryam Esmaeilzadeh; Azin Alizadeasl; Arash Hashemi (Journal of Tehran University Heart Center, 2015)
Bifid cardiac apex is a rare anomaly of human hearts. We report of the case of a 34-year-old man with a previous history of ventricular septal defect (VSD) and subvalvular pulmonary stenosis. He had undergone pulmonary commissurotomy and VSD closure 22 years before he was referred to our center for evaluation of progressive dyspnea. Transthoracic echocardiography revealed atrial septal defect (ASD), multiple VSDs, severe pulmonary regurgitation, and a bifid cardiac apex. The patient was referred for re-do surgery for ASD and VSD closure along with pulmonary valve replacement, but he refused the surgery.